Konsep Manusia dan Budaya dalam al-Qur'an - Fathiya Sukma Prafana; Fikramsyah Putra Ramadhan; Natasya Ziqra Anggrainni; Annisatul Husna (Fakultas Ushuluddin dan Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2023)
This article aims to analyze human concepts, culture and the relationship between the two according to the Koran. This research was carried out using a literature review with a descriptive-analysis method, namely by collecting data from several existing sources and then explaining it again. In this research it was found that human concepts can be analyzed from several words in the Koran such as the words insan, basyar, and nas, ins, all four of which have different meanings according to the function of their use in the Koran. Apart from the human concept, this research also puts forward the cultural concept in the Koran, namely referring to the word